Maximizing Weed Control in Florida Citrus - Stephen H. Futch; Brent Sellers (EDIS, 2015)
With Florida citrus growers and production managers being “squeezed” between rising production prices and declining yields from citrus greening, there’s more call than ever to reduce citrus production costs. Controlling weeds is a major expense, amounting to 11% of the total $2,278 annual production cost per acre for the 2014–2015 season. This revised 3-page fact sheet teaches the six essential components of an effective weed-management program to help maintain the profitability of this vital Florida industry. Written by Stephen H. Futch and Brent Sellers, and published by the Horticultural Sciences Department, September 2015.